Prototype Model Classification System Level Internal Audit Findings Based on Case-Based Reasoning in Education Quality Management - Marzuki Marzuki; Maria Shusanti Febrianti (Bandar Lampung University (UBL), 2014)
This research aims to assure and improve the quality of education in educational institutions in the process of implementing the internal audit continuity with the classification based on audit findings CBR (Case Base Reasoning). Because there are times when the auditor is less precise in determining the appropriate classification level in giving findings on the findings resulting from the audit process itself. Levels of these findings consists of Major and Minor deficiency findings deficiency findings. Major deficiency findings that internal control weaknesses in the company which resulted in barriers to an organization on a unit within the organization to achieve the goals set. While Minor deficiency findings of internal control weaknesses in the company, which, although not to obstruct the achievement of the objectives of an organizational unit but need to be reported to management because if not corrected could hurt the company. In classifying the audit findings, the auditor should be given a long experience (case) in order to solve or make predictions about what might happen in a new situation or a problem with comparing the old and adjusting to the situation to see where the new situation is most suitable, it requires Case-Based reasoning means reasoning based on remembering previous experiences, a new problem is solved by considering the solution of old problems and then adapt the solutionto find the requirement softoday's problems.